Design and optimisation of fullerene-based nanoemulsion system for nanocosmeceutical applications - Ngan, Cheng Loong (2015)
Fullerene is gaining interest as an antioxidant in the cosmetic industry but the primary challenges are the incorporation of fullerene due to its hydrophobicity and difficulties in formulating a stable carrier system. Newly developed nanoemulsion system was designed specifically for transdermal application in cosmeceutical applications. Pseudoternary phase diagrams were constructed to serve as platform in building an emulsion system which constituted of palm kernel oil esters (PKOEs), non-ionic surfactant(s), water and fullerene as bioactive ingredient. Non-ionic surfactants applied were polyoxyethylene sorbitan monooleate (Tween 80) and sorbitan monooleate (Span 80) with different mixed surfactant ratios (MSRs). Based on the results, binary surfactant system of Tween 80:Span 80 with MSR of 8:2 performed better in emulsification capability by exhibiting larger monophasic region compared to the usage of single surfactant. The hydrophilic-lipophilic balance value of mixed surfactant unveiled the largest homogeneous and isotropic regions is 12.86. Compositions selected from pseudoternary phase diagrams were designated as pre-formulation. Excipients contained alongside within the formulation include xanthan gum as rheology modifier, beeswax as emollient and phenonip as anti-microbial agent. Nanoemulsions were prepared by high shear homogeniser, followed by ultrasonic cavitation. The physicochemical behaviours of formulations with various proportions of components were extensively characterised. Essentially, the mean particle size was in the nanosize range of 70-160 nm. It was found that xanthan gum amount with 0.60% (w/w) or higher was able to stabilise the emulsion droplets by forming polymer network with steric stabilising effect. The effect of composition on nanoemulsion; PKOEs, surfactants and xanthan gum amount on variation of particle size, ᶘ-potential and viscosity were investigated. Multivariate statistical techniques such as response surface methodology (RSM), Box-Behnken (BBD) and central composite rotatable (CCRD) designs were used to optimise the formulation in acquiring desirable properties of nanoemulsion system. The optimum formulation comprised 12.50% of PKOEs, 7.68% of Tween 80:Span 80 (4:1) and 0.90% of xanthan gum yielded a particle size, ᶘ-potential and viscosity of 153.6 nm, −53.4 mV and 42.1 Pa s, respectively. Linear relationships were observed in all cases where no interaction occurred between the variables. According to the pareto graphic analysis, surfactant amount gave the largest effect on particle size and ᶘ-potential whereas viscosity was largely dependent on xanthan gum amount. Second stage of optimisation was performed to discover the influence of process parameters on the similar responses as investigated earlier. The effect of process types on response variables was complex being dependent on the existence of interaction between the parameters (quadratic polynomial model). The results showed that nanoemulsion prepared under homogenisation rate of 4352 rpm and sonication amplitude of 48% for 97 s would produce particle size, ᶘ-potential and viscosity of 152.5 nm, −52.6 mV and 44.6 Pa s, respectively. Interestingly, in both optimisation designs, CCRD demonstrated excellent model fitting and estimation of actual values than BBD with lower residual standard error. Nonetheless, both designs predicted similar responses which affirmed one another in terms of reliability to obtain optimum formulation with improved attributes. Rheological behaviour of nanoemulsion was evaluated using viscometry test. From the rheograms, nanoemulsion exhibited shear thinning (pseudoplastic) behaviour which obeys the power law model. The results from oscillatory strain sweep test showed the wide linear viscoelastic region which directly correlated to high rigidity of the system. The architecture of the nanoemulsion system was analysed using transmission electron microscope to study the morphology. The micrographs showed that the particle size was in agreement with the measured size. In the physical stability and thermal stress test, the optimum formulation was stable under high centrifugal force, storage at room temperature and 45°C for 90 days while maintaining its nano-sized particle and high ᶘ-potential with texture and consistency being preserved. Likewise, the colloidal system was able to withstand freeze-thaw cycles and having low rate of Ostwald ripening. In the safety evaluation test, nanoemulsion showed no cytotoxicity effect on fibroblast cell (3T3) up to 48 hours. Results also showed that nanoemulsion was non-irritant with Human Irritancy Equivalent (HIE) scores of 0.36. In vivo biophysical attributes of skin studies showed that the skin hydration increased without any increase in transepidermal water loss up to 28 days of the treatment period. However, with this finding, the skin hydration increased more progressively on application of fullerene-laden formulation compared to placebo (without fullerene). Collagen content was increased significantly which lead to improved water binding capacity. No visible skin reactions caused by dermal irritation, contact sensitisation or rash were experienced by the subjects during the treatment. This work concluded that a stable fullerene nanoemulsion fits for cosmetic was successfully developed and showed potential collagen regeneration in human skin.